PdRu bimetallic nanoalloys with improved photothermal effect for amplified ROS-mediated tumor therapy - Liang, Yujia; Ning, Shufang; Kurboniyon, Mekhrdod S.; Rahmonov, Khaiyom; Cai, Zhengmin; Li, Shirong; Mai, Jinling; He, Xiaojing; Liu, Lijuan; Tang, Liping; Zhang, Litu; Wang, Chen (Frontiers in Bioengineering and Biotechnology, 2025)
An emerging strategy in cancer therapy involves inducing reactive oxygen species (ROS), specifically within tumors using nanozymes. However, existing nanozymes suffer from limitations such as low reactivity, poor biocompatibility, and limited targeting capabilities, hindering their therapeutic efficacy. In response, the PdRu@PEI bimetallic nanoalloys were constructed with well-catalytic activities and effective separation of charges, which can catalyze hydrogen peroxide (H2O2) to toxic hydroxyl radical (·OH) under near-infrared laser stimulation. Through facilitating electron transfer and enhancing active sites, the enhanced peroxidase-like (POD-like) enzymatic activity and glutathione (GSH) depletion abilities of nanozymes are boosted through a simple co-reduction process, leading to promising anti-tumor activity. The electron transfer between Pd and Ru of PdRu@PEI nanoalloys contributes to POD-like activity. Then, by oxidizing endogenous overexpressed GSH, enzymatic cycling prevents GSH from consuming ROS. Furthermore, the surface plasmon resonance effect of near-infrared laser on bimetallic nanoalloys ensures its photothermal performance and its local heating, further promoting POD-like activity. The integrated multi-modal therapeutic approach of PdRu@PEI has demonstrated significant anti-cancer effects in vivo studies. The nanozymes exhibit high catalytic efficiency and excellent biocompatibility, offering valuable insights for the development of nano-catalysts/enzymes for biomedical applications.